A Radical - Transformational Change Through Leadership (Malaysian Management Journal, 2005)
This paper is concerned with leadership practices in a radical process change, namely, business process reengineering (BPR). The paper looks at the higher education context, which has successfully implemented BPR in their key processes. The results were taken from three in-depth case studies using the triangulation approach which includes open-ended interviews and use of secondary data. The results had shown six important leadership factors as key drivers to enable process change to happen successfully. Leaders need to be able to practise different leadership approaches or styles based on situations, emphasise on a strategic vision, use effective communications, do reinforcement, give commitment and support, and have leadership qualities. Some suggestions regarding leadership best practices for a radical transformational change are also outlined.